Relevansi Tujuan Dan Materi Dalam Diklat Guru Di SMP Negeri 2 Batu Belah - Dahrani, Dahrani; busra, Aminudin; Rizadiliyawati, Rizadiliyawati; Afriza, Afriza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Education is a major pillar in the development of a country, and the quality of education in Indonesia is highly dependent on teacher competence. This study analyzes the relevance of objectives and materials in teacher education and training (diklat) programs at SMP Negeri 2 Batu Belah. Using a qualitative approach and case study design, data were collected through in-depth interviews, observations, and document analysis. The results of the study indicate that although the training program has benefits in improving teacher competence, there are significant challenges, such as the inconsistency of the materials with practical needs in the field and the lack of training in the use of digital technology. In addition, theoretical training materials provide less opportunity for teachers to develop practical skills. This study recommends the need for updating training materials that are more relevant and in accordance with the specific needs of teachers, as well as improving evaluation and feedback to support the effectiveness of training programs in improving the quality of teaching in schools